Hexamethyldisilazane-assisted Mn2+ doping of perovskite nanocrystals under ambient conditions. Issue 9 (15th February 2022) - Hu, Kaiwen; Hu, Yongfei; Li, Tan; Qiao, Fen; Chen, Yunxia; Han, Jianjun; Li, Lee; Ali, Ghafar; Xie, Yi
Abstract : Mn 2+ doping into lead halide perovskite nanocrystals via a hexamethyldisilazane-assisted procedure under ambient conditions to tune the optical properties. Abstract : Doping Mn 2+ ions into lead halide perovskite (LHP) nanocrystals (NCs) has attracted great attention in the optoelectronic fields due to the stability enhancement and unique dual-color emission characteristics arising from the energy transfer from the LHP host to the dopants ( i.e., Mn 2+ ions). Herein, we report a facile and scalable synthetic protocol for Mn 2+ -doped CsPbCl3 and CsPbBr x Cl3− x nanoplates via a one-pot room-temperature (RT) procedure in the presence of hexamethyldisilazane (HMDS). It is noteworthy that both HMDS and Mn 2+ ions play a critical role in triggering the crystallization of the Mn-doped LHP NCs under ambient conditions by functioning as a passivation agent with Lewis base groups that coordinate with Pb 2+ ions. The optical properties including the emission wavelength and the relative PL intensity of the band-to-band emission and the Mn 2+ emission are tuned by changing the amount of HMDS and the precursor ratios Mn : Pb and Br : Cl. It is interesting that the representative Mn-doped CsPbCl3 NCs displayed enhanced thermal stability, which was confirmed by the observation that the emission intensity of the sample annealed below 95 °C for 2 h increases compared with that of the fresh sample. Ion exchanges between not only Cl −, Br − and I − but also Mn 2+ and Pb 2+ are also investigated.